2021
DOI: 10.3390/ijerph18041593
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Consumers’ Online/Offline Shopping Behaviours during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has wreaked havoc in Korean society since the end of 2019. Unlike prior to the pandemic, when online and offline activities were conducted side-by-side, many aspects of consumers’ daily lives are only conducted online, especially shopping and meetings. This study analysed the characteristics of consumers who have used offline shopping channels during the pandemic. In addition, participants were asked how often they will use online and offline shopping channels after society stabilizes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 29 publications
(42 reference statements)
3
109
0
3
Order By: Relevance
“…Some respondents avoid purchasing at physical stores since a lot of people do not follow the SOP and social distance. People who did not comply with the SOP tend to use the traditional shopping method and this situation has diminished other people's desires to use it to avoid exposure to the virus (Moon, Choe & Song, 2021). Table 3 shows the respondent's perceptions towards online shopping methods.…”
Section: Resultsmentioning
confidence: 99%
“…Some respondents avoid purchasing at physical stores since a lot of people do not follow the SOP and social distance. People who did not comply with the SOP tend to use the traditional shopping method and this situation has diminished other people's desires to use it to avoid exposure to the virus (Moon, Choe & Song, 2021). Table 3 shows the respondent's perceptions towards online shopping methods.…”
Section: Resultsmentioning
confidence: 99%
“…Consumer behaviors changed under different stages of the pandemic, across different countries and areas, and under different governmental policies. Individual differences influenced consumers' channel selections [98]. In a recent study, researchers investigated apparel consumers' channel shifting intentions during the COVID-19 pandemic and discovered that perceived vulnerability (PV) affected consumers' attitude toward shifting to online channel from physical channel [53].…”
Section: Behavioral Responses and Moderating Effect Of Perceived Covid-19 Vulnerabilitymentioning
confidence: 99%
“…Perceived vulnerability is the key concept in the protection motivation theory for measuring threat appraisals (the degree of risk of perilous actions) [99]. Moon et al [98] revealed that perceived vulnerability and offline-channel use intention were negatively correlated. BOPI and BOCP services could help reduce the searching and browsing time consumers might spend in physical stores or even skip the offline channel (walk-ins) to receive orders.…”
Section: Behavioral Responses and Moderating Effect Of Perceived Covid-19 Vulnerabilitymentioning
confidence: 99%
“…Even after COVID‐19, consumers said they would wear masks, and most said that only basic makeup can be done while wearing masks 17 . In the presence of severe external influences including serious prevalence of infectious diseases such as SARS or COVID‐19, the consumption patterns of consumers have been changing or expanding into the paradigm of online shopping channels than making offline purchases 18 . Table 1 summarizes beauty purchasing activities that have changed from offline to online due to COVID‐19.…”
Section: Resultsmentioning
confidence: 99%